La cuestión (de la) técnica. Variantes culturales y estéticas. (2014)
This paper, thinking about technique, runs several scenarios that integrate forms of apprehension of the human and its integration into the cultural evolution. The technique overlaps the use of objects and devices, as well as coding systems that allow a social articulation of a zitgeist of the the contemporary, whether at a discursive level or in the socio-economic and cultural practices. This paper aims to present an overview about contemporary meanings of the concept of technique, based on etymological details and historical contextualization in order to find a functional transversality linking it to aesthetic axes in an expanded sense, defining a cultural appropriation of the phenomenon .